Eco-Innovation and Ethical Certification: A Dual Pathway to Competitive Advantage For F&B Enterprises - Purba, Indra Setiawan; Ariwibowo, Prasetio (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The study aims to test the dual impact of two independent variables (Sustainable Product Differentiation and Ethical Certification) on a dependent variable (Profit Margins), mediated by Customer Loyalty. The research adopts a quantitative, cross-sectional, survey-based methodology aimed at measuring the sustainable practices of micro food and beverage businesses. The quantitative approach facilitates the systematic collection and analysis of numerical data to identify patterns or relationships among the constructs being studied. The data collection technique in this study used a survey instrument developed based on existing literature, which provides a robust framework for measuring key constructs related to sustainability practices and consumer perceptions.The data analysis technique in this study is Variance-Based Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0, justifying its use for predictive research and theory development in complex models. The results of this study show that the coefficient value obtained is 0.265 with a T-statistic of 4.902 and a p-value of 0.000. Because T>1.96 and p<0.05, Certification (X2) has a significant indirect effect on Profit Margin (Y). This means that Loyalty (Z) significantly (fully) mediates the effect of Certification (X2) on Profit Margin (Y). And with a coefficient value of 0.467 with a T-statistic of 8.455 and a p-value of 0.000. With T <1.96 and p> 0.05, Differentiation (X1) has a significant indirect effect on Profit Margin (Y). This means that Loyalty (Z) significantly (fully) mediates the effect of Differentiation (X1) on Profit Margin (Y).